'Joining the Dots: Linking Prenatal Drug Exposure to Childhood and Adolescence' - research protocol of a population cohort study - Barbara Bajuk; Charles Green; Andrew Page; John Eastwood; Ju Lee Oei; Mithilesh Dronavalli; Lucinda Burns; Evelyn Lee; Michelle Dickson; Kate Lawler; Hannah Uebel; Lauren Dicair (BMJ Publishing Group, 2024)
Introduction Prenatal drug exposure (PDE) is one of the most important causes of child harm, but comprehensive information about the long-term outcomes of the families is difficult to ascertain. The Joining the Dots cohort study uses linked population data to understand the relationship between services, therapeutic interventions and outcomes of children with PDE.Methods and analysis Information from routinely collected administrative databases was linked for all births registered in New South Wales (NSW), Australia between 1 July 2001 and 31 December 2020 (n=1 834 550). Outcomes for seven mutually exclusive groups of children with varying prenatal exposure to maternal substances of addiction, including smoking, alcohol, prescription/illicit drugs and neonatal abstinence syndrome will be assessed. Key exposure measures include maternal drug use type, maternal social demographics or social determinants of health, and maternal physical and mental health comorbidities. Key outcome measures will include child mortality, academic standardised testing results, rehospitalisation and maternal survival. Data analysis will be conducted using Stata V.18.0.Ethics and dissemination Approvals were obtained from the NSW Population and Health Services Research Ethics Committee (29 June 2020; 2019/ETH12716) and the Australian Capital Territory Health Human Research Ethics Committee (11 October 2021; 2021-1231, 2021-1232, 2021-1233); and the Aboriginal Health and Medical Research Council (5 July 2022; 1824/21), and all Australian educational sectors: Board of Studies (government schools), Australian Independent Schools and Catholic Education Commission (D2014/120797). Data were released to researchers in September 2022. Results will be presented in peer-reviewed academic journals and at international conferences. Collaborative efforts from similar datasets in other countries are welcome.